The effectiveness of implementation experential learning model with scaffolding technique (MELS) to increase the critical thinking ability - Ismail Ismail; Abd Muis (Seminar Nasional LP2M UNM, 2019)
The purpose of this research is to know the level of students critical thinking ability and the effectiveness of implementation MELS learning model on students Biologi Education Program in MIPA Faculty UNM. This research used One-Group Pretest-Posttest Design. The instrument in this research used essay test to measure 9 indicators critical thinking ability. Data collectiion using instrument test critical thinking for Pre Test and Post Test, observation sheets to observe of learning feasibility, observation sheet to observe students’ activity, and questionnaire of students response. The data analysis by descriptive statistical technique and inferential statistical. The result as follows: (1) pretest average of students critical thinking ability is 16.94 in the low category with standart deviation 5.13. Minimum value is 8 and maximum value is 37 from score ideal 72. As for posttest average of students critical thinking is 54.94 in the medium category with standart deviation 7.57. Minimum value is 20 and maximum value is 66 from ideal score 72. In addition, the increase of students critical thinking ability shown that the average score of normlized gain is 0.69 in high category. (2) the average score of learning feasiblity is 3.5, in well implemented category. (3) the average score of students activity is 3.5 in very good category. (4) the average score of response students toward MELS learning model is 3.2 with tends to positive response category.